2023
DOI: 10.1108/ijtc-05-2022-0144
|View full text |Cite
|
Sign up to set email alerts
|

How does a hotel’s hygiene protocol quality trigger guests’ revisit intention during the pandemic? Evidence from Chinese guests

Abstract: Purpose Based on the Stimulus-Organism-Response Model, this study aims to investigate how the intention of Chinese guests to revisit a hotel (response) is triggered by the quality of the hotel’s hygiene protocols (stimulus) during the pandemic. Brand image, perceived guest satisfaction and perceived customer trust were examined as the organism factors in this model. Design/methodology/approach The quantitative method was adopted to collect data via a structured online survey of 385 Chinese hotel guests. Thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 115 publications
(144 reference statements)
1
1
0
Order By: Relevance
“…Secondly, hygiene control has a significant negative moderating effect on the negative impact of luxury hotel customers' perceived risk and revisit intentions, according to the moderating effect plot shown in Figure 4 that when luxury hotel customers' attention to the importance of hygiene control is at a low level, the negative relationship between their perceived risk and revisit intention is stronger. The same can be confirmed to some extent by Yu, Seo et al (2021) and Islam et al (2023).…”
Section: Discussionsupporting
confidence: 68%
“…Secondly, hygiene control has a significant negative moderating effect on the negative impact of luxury hotel customers' perceived risk and revisit intentions, according to the moderating effect plot shown in Figure 4 that when luxury hotel customers' attention to the importance of hygiene control is at a low level, the negative relationship between their perceived risk and revisit intention is stronger. The same can be confirmed to some extent by Yu, Seo et al (2021) and Islam et al (2023).…”
Section: Discussionsupporting
confidence: 68%
“…According to Wanjau (2012), lower staff competencies resulted in a drop in the provision of quality services [14]. Durdyev Business, management and accounting that the workforce cluster of abilities, competencies, and experiences, as well as the work management cluster of communication among parties, positively impacted service delivery [73,74]. Durdyev et al…”
Section: Personal Factors and Service Deliverymentioning
confidence: 99%
“…For example, in a themed restaurant setting Meng and Choi [42] found that the physical servicescape of the restaurant like decoration, ambience and layout of the furniture had positive effect on satisfaction of customers. In hoteling context consumer satisfaction is of utmost importance because on it depends whether the consumer will purchase the service again and hold revisit intentions [43,10]. Alfakhri et al [44] conducted a phenomenological study in United Kingdom and found for the most part customers derived their satisfaction from aesthetics and design aspects of hotel servicescape.…”
Section: Servicescape and Satisfactionmentioning
confidence: 99%